Horta suspensa na escola - Reis, Ana Serafim dos; Silvério , Agda Rodrigues Rios; Gonçalves, Genilza Aparecida; Lima, Eliene Xavier de; Santana, Lusmar Moreira de Azevedo; Alencar, Rosânia Aparecida; Botassim, Rosa Maria Ferreira (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf